2008
DOI: 10.1002/anie.200802161
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthesis of a Glycosylphosphatidylinositol‐Anchored Prion Protein

Abstract: Pinning down the role of the anchor: The chemical synthesis of a cysteine‐modified glycosylphosphatidylinositol (GPI) anchor provides access to homogeneous GPI‐anchored prion protein through expressed protein ligation (see scheme). By this method, it should be possible to investigate the influence of the complex posttranslational GPI modification on protein structure and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 47 publications
0
71
0
4
Order By: Relevance
“…We have successfully extended our previously developed expressed protein ligation strategy to generate multimilligram amounts of three different PrP variants. Our previous results demonstrate that homogeneous, folded PrPs equipped with a membrane anchor behave similarly to GPI-modified PrP in vitro (23), and they have allowed us to address several questions about the membrane interaction and conformational changes of PrPs.…”
Section: The C-terminal Membrane Anchor Strongly Influences the Biochmentioning
confidence: 90%
See 2 more Smart Citations
“…We have successfully extended our previously developed expressed protein ligation strategy to generate multimilligram amounts of three different PrP variants. Our previous results demonstrate that homogeneous, folded PrPs equipped with a membrane anchor behave similarly to GPI-modified PrP in vitro (23), and they have allowed us to address several questions about the membrane interaction and conformational changes of PrPs.…”
Section: The C-terminal Membrane Anchor Strongly Influences the Biochmentioning
confidence: 90%
“…7). These results suggest that attaching PrP constructs via their C-terminal membrane anchor helps the N-terminal polybasic region of PrP (residues [23][24][25][26][27], which is lacking in the T_PrP construct, to enhance the electrostatic interaction of PrP with anionic phospholipid membranes. Indeed, Wang et al (33) already determined that this region initiates (electrostatic) interaction between PrP and anionic phospholipids.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…26,35,37,102 A possible solution is the chemical synthesis of representative diacylglycerophosphoinositolglycan species, but currently these methods are complicated and not well applicable for protein anchoring. 103,104 An example of this problem is to set up appropriate experiments for answering how important the GPI-anchoring is in the basic PrP Sc replication process. The demand for membrane associated PrP analogues inspired huge efforts to prepare semisynthetic lipo-PrP derivatives (Figure 6).…”
Section: Synthetic Glycosylphosphatidylinositol Analoguesmentioning
confidence: 99%
“…100,101,105,106 Beyond, the fluorescent protein GFP was also used to demonstrate the membrane anchoring properties of such synthetic lipids. 93,94,100,101,103,[105][106][107][108][109] It was found that the removal of the carbohydrate moiety or its truncation can retain the anchoring function of the GPIs.…”
Section: Synthetic Glycosylphosphatidylinositol Analoguesmentioning
confidence: 99%